Food Composition of Little Tunny Euthynnus alletteratus (Rafinesque,1810) in the Marine Waters of Lattakia – Syria - GALIYA, Mohamad; Eddin Laika, Hussam; Almajid, Zouher; Othman, Ranim (Journal of Marine and Coastal Science, 2025)
The current research aims to study the diet of 275 individuals from Euthynnus alletteratus, caught in the marine waters of Lattakia Governorate for two years (19/10/2021 - 29/9/2023), using local fishing methods (gill nets, purse nets, fixed nets, and long lines). The results of the food spectrum showed a similarity in their feeding habits and behaviors, as they are carnivorous fish. The food spectrum consists of four taxonomic groups: Fish, Crustaceans, Molluscs, and Annelids. The species E. alletteratus fed on 18 food elements during the first year (2021-2022) and 28 food elements in the second year (2022-2023). Fish formed the first group, with seven species in the first year and 17 species in the second year. It is known that there were Crustaceans in 5 taxonomic groups: (Amphipoda, Decapoda, Stomatopoda, Euphausidae, Isopoda), Molluscs, and Polychaete. It has been also observed that individuals of E. alletteratus respond to seasonal changes in food availability, which reflect their adaptation ability to feed on the most abundant species in the environment. They fed on Crustaceans as their main prey in the Autumn (90%) and winter (97%), followed by fish in the Spring (67%) and Summer (69%), while Molluscs and Annelid enhanced their diet. This reflects the poor food base for fish in our marine environment.